Cloud computing and services sciences : International Conference in Cloud Computing and Services Sciences, CLOSER 2014, Barcelona Spain, April 3-5, 2014, Revised selected papers /: International Conference in Cloud Computing and Services Sciences, CLOSER 2014, Barcelona Spain, April 3-5, 2014, Revised selected papers. (2015) - Unknown
No abstract available